ALAT PENGATUR WAKTU SECARA WIRELESS DENGAN MEDIA INFRARED - Adrianto, H; Hartono, H; Jefri, Jefri (Universitas Tarumanagara, 2008)
All workers in the factory can change the timer on machine, it can make a disadvantage for the factory Based on this consideration, it is necessary to make a tool that can be used to control the timer wireless by infrared. In the end, by using this tool, only people who responsible about the production of machine can change the timer.